SYNTHESIS AND ANTICONVULSANT ACTIVITY OF 2-SUBSTITUTED-5-CHLOROBEN ZOXAZOLE (Biological Sciences - PJSIR, 2002)
The  potassium   salt(l)  of  5-chlorobenzoxazole-2-thione  was  prepared  and  allowed  to  react with  alkyl  chloroacetate and alkyl  3-chloro-propiona te  to  afford  ll _12 1 10 .Compound 112 was  allowed  to  react  with a mmonia  and  hydrazine hydrate to 11 afford 111 and  III respecti vely.  The compound 11112 was  also  reacted  with  the  appropiate  aldehydes  to  afford com 13 pound s N _ w  The potassium  salt(l)  was  also  reacted  with  chloro-acetanilides  to  afford  compound s V 20_39 .   Preliminary pharmacologi cal testing of some of these compounds showed that they exhibit anticonvulsant activity. The structu re of  these compound s was  confirmed  by elemental  analysis JR, 1HNMR  and  in  some cases by MS  spectral  data .